Harmonization of Human Rights Principles and Maqasid Syari'ah in The Issue of Interreligious Marriages (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2025)
This research examines the issue of interreligious marriage in Indonesia through the perspective of Human Rights (HAM) principles and Maqasid al-Shari‘ah (objectives of Islamic law). Although the practice of interreligious marriage continues to increase, its legal certainty remains unclear, leading to theological, social, and administrative problems. Human Rights guarantee freedom of religion and the right to marry, but their implementation in Indonesia must be aligned with the Marriage Law, religious norms, and the values of Pancasila (ideology). This research employs a literature review with content analysis and positions Maqasid al-Shari‘ah as an analytical framework to assess the maṣlaḥah (benefit) and mafsadah (disadvantage) of interreligious marriage based on the al-ḍarūriyyāt al-khams (five essential objectives of Islamic law). The findings show that restrictions on interreligious marriage are not a form of human rights violation but rather a mechanism to protect religious identity, family stability, the legal status of children, and the social order. The study concludes that Human Rights and Maqasid al-Shari‘ah share an orientational meeting point: the protection of human dignity and the promotion of public welfare. Therefore, harmonization can be achieved through a proportional legal approach, protection of vulnerable parties, and a legal interpretation responsive to Indonesia’s socio-religious context.